Macrophage IL-1β-positive microvesicles exhibit thrombo-inflammatory properties and are detectable in patients with active juvenile idiopathic arthritis - Cambon, Audrey; Rebelle, Charlotte; Bachelier, Richard; Arnaud, Laurent; Robert, Stéphane; Lagarde, Marie; Muller, Romain; Tellier, Edwige; Kara, Yéter; Leroyer, Aurélie; Farnarier, Catherine; Vallier, Loris; et al. (Frontiers in Immunology, 2023)
Objective IL-1β is a leaderless cytokine with poorly known secretory mechanisms that is barely detectable in serum of patients, including those with an IL-1β-mediated disease such as systemic juvenile idiopathic arthritis (sJIA). Leukocyte microvesicles (MVs) may be a mechanism of IL-1β secretion. The first objective of our study was to characterize IL-1β-positive MVs obtained from macrophage cell culture supernatants and to investigate their biological functions in vitro and in vivo. The second objective was to detect circulating IL-1β-positive MVs in JIA patients. Methods MVs were purified by serial centrifugations from PBMCs, or THP-1 differentiated into macrophages, then stimulated with LPS ± ATP. MV content was analyzed for the presence of IL-1β, NLRP3 inflammasome, caspase-1, P2X7 receptor, and tissue factor (TF) using ELISA, Western blot, or flow cytometry. MV biological properties were studied in vitro by measuring VCAM-1, ICAM-1, and E-selectin expression after HUVEC co-culture and factor-Xa generation test was realized. In vivo, MVs’ ability to recruit leukocytes in a murine model of peritonitis was evaluated. Plasmatic IL-1β-positive MVs were studied ex vivo in 10 active JIA patients using flow cytometry. Results THP-1-derived macrophages stimulated with LPS and ATP released MVs, which contained NLRP3, caspase-1, and the 33-kDa precursor and 17-kDa mature forms of IL-1β and bioactive TF. IL-1β-positive MVs expressed P2X7 receptor and released soluble IL-1β in response to ATP stimulation in vitro. In mice, MVs induced a leukocyte peritoneal infiltrate, which was reduced by treatment with the IL-1 receptor antagonist. Finally, IL-1β-positive MVs were detectable in plasma from 10 active JIA patients. Conclusion MVs shed from activated macrophages contain IL-1β, NLRP3 inflammasome components, and TF, and constitute thrombo-inflammatory vectors that can be detected in the plasma from active JIA patients.